IDENTIFICATION OF HARD ROCK BASED ON SHALLOW SEISMIC INTERPRETATION AND SPT TEST FOR FOUNDATION OF BRIDGE AT BALANG ISLAND, BALIKPAPAN BAY, EAST KALIMANTAN - Ediar Usman; Kris Budiono (Bulletin of the Marine Geology, 2017)
The study area is located in Balikpapan Bay, the connecting waters between Pancur village at the southwest and Balang Island at the northeast. The objective of study is to know the engineering properties of rock as a foundation groundwork of bridge. Result of seismic reflection interpretation profiles in the survey area indicates that the seismic sequences can be divided into two sequences, those are sequence A and B. Sequence A lies at the upper part, which is characterized by concordance, parallel, wavy and hummocky reflectors. Sequence B is characterized by mounded, chaotic and free reflectors. Sediment thickness obtained from seismic profiles show that Quaternary sediment is about 1.56 to 4.89 meters, while harder substrate thickness ranging between 7.03 and 21.60 meters. While, based on core drilling data, hard rock started to appear between 3 and 4 meters below seafloor with Standard Penetration Test (SPT) between 32 and 34 blows as Tertiary sediments. Based on field observation and correlated with geological map of Balang Island, Balikpapan Sheet, the hard rock proposed for base of bridge foundation is Balang Island Formation (Middle Miocene) that consist of claystone, sandstone and coal layers that have been deformated and start to form fold as anticline. The seismic record show that, the hard rock is interpreted as B sequence that underlain by Quaternary sediments.